Three consecutive recurrent ectopic pregnancy-A Case Report (Northern International Medical College Journal, 2022)
Ectopic pregnancy (EP) is a potentially life-threatening condition, leads to increased maternal mortality and morbidity till date. About 2% of all pregnancies are Ectopic one and recurrence rate is as high as 1 in every 10 pregnancies. Here we present a case who had a history of 2 Ectopic pregnancies – 1st one treated surgically and 2nd one by medical method. Unfortunately, 3rd pregnancy was also an Ectopic one and needed surgical management. Thus, her natural reproductive ability went down and had to go for In vitro fertilization (IVF) pregnancy and successfully got twin baby (Girl, on March,2020).Northern International Medical College Journal Vol. 12 No.1 July 2020, Page 511-514